Leaching and heating process as alternative to produce fish protein powder from Kilka (Clupeonella cultiventris caspia) - RAHMANIFARAH, KAVEH; SHABANPOUR, BAHAREH; SHAVIKLO, AMIR REZA; AALAMI, NEHRAN (Nusantara Bioscience, 2016)
Abstract. Rahmanifarah K, Shabanpour B, Shaviklo AR, Aalami M. 2014. Leaching and heating process as alternative to produce fish protein powder from Kilka (Clupeonella cultiventris caspia). Nusantara Bioscience 6: 1-6. The effect of protein extraction procedures (leached mince and heated suspension) on selected properties of fish protein powder (proximate composition, pH, color, density, viscosity, fat adsorption, emulsifying capacity, emulsifying stability, foaming capacity, foaming stability, WBC, protein solubility in water, hygroscopicity, Trichloroacetic acid (TCA)-soluble peptides and free sulfhydryl groups) was investigated. Results showed that Fish protein powder (FPP) produced by leaching mince (LM) have higher protein, moisture, ash, pH, L*, viscosity, emulsion capacity, emulsion stability, foam capacity, foam stability, water binding capacity (WBC), protein solubility, hygroscopicity, TCA soluble peptides and free sulfhydryl group content than heated suspension (HS) (P
Keywords: Fish protein powder; functional properties; kilka; leaching; suspension